2003
DOI: 10.1007/s00266-003-2070-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Tip Nasal Muscles and the Short Upper Lip

Abstract: Since 1993 the authors have been using a new approach to the treatment of the muscles intimately related with the nasal tip and the upper lip, today known as dynamic rhinoplasty. With the idea of improving the dorsum-tip-labial relationship, the dynamic rhinoplasty technique is based on performing an intraoral zetaplasty at the labial frenum, allowing the access to the local musculature, represented by the depressor septi nasi muscle and its three fascicles. Next, we perform a subperiosteal undermining of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 3 publications
0
20
0
1
Order By: Relevance
“…Depending on the approach of the dissection, the origin of the muscle is considered to be at the maxilla, above the incisors, when a gingival approach is used but attributed to the orbicularis oris when a top-down dissection is used. 11,12 It is often considered a part of the myrtiformis or a small attachment of the orbicularis oris. In 1998, de Souza Pinto et al 13 On the basis of our dissections, we found distinct paired DSN muscles originating from the maxilla directly above the central incisor in 14 of 15 cadavers ( Figure 6).…”
Section: Depressor Septi Nasalismentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the approach of the dissection, the origin of the muscle is considered to be at the maxilla, above the incisors, when a gingival approach is used but attributed to the orbicularis oris when a top-down dissection is used. 11,12 It is often considered a part of the myrtiformis or a small attachment of the orbicularis oris. In 1998, de Souza Pinto et al 13 On the basis of our dissections, we found distinct paired DSN muscles originating from the maxilla directly above the central incisor in 14 of 15 cadavers ( Figure 6).…”
Section: Depressor Septi Nasalismentioning
confidence: 99%
“…15,16 One group defined it as the nasalis portion of the transverse nasalis, 10 another described it as the deep layer of the levator labii superioris, 11 and still others have considered it a separate muscle. 17 On the basis of our dissections, we consider it a distinct muscle with its origin from the maxilla at the level of the canine tooth, just lateral to the origin of the myrtiformis muscle and medial to the origin of the transversalis muscle (Figure 7).…”
Section: Dilator Narismentioning
confidence: 99%
“…These results are in contrast to the current literature. During the past two decades, a few surgeons have introduced several surgical techniques that also address the depressor septi nasi muscle during rhinoplasty [11][12][13][14]. Each of these studies has manipulated this muscle in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…This method involves en bloc removal of soft tissue, including the depressor septi muscle, through a full-thickness diamond-shaped excision between the feet of the medial crura, allowing direct visualization and suture plication of splayed medial crura. De Souza Pinto [13] reported his ''dynamic rhinoplasty'' technique. He combined release of the medial fasciculi of the depressor septi with either horizontal or vertical plication of the intermediate fasciculi, depending on whether the patient has a short or a long upper lip, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation